International Conference of the Asian Academy of Applied Business (AAAB) 2005 : capitalising the potential of the asian integrated market, 28 - 30 July, 2005 Bumi Minang Hotel, Padang, Sumatera Barat, Indonesia : [proceedings] - Proceedings of the International Conference of the Asian Academy of Applied Business (AAAB) (2nd : 2005 : Sumatera Barat, Indonesia) (West Sumatra, Indonesia : Asian Academy of Applied Business, 2005)
Includes bibliographical references